Knowledge and attitudes of Croatian Dentists Regarding Antibiotic Prescription in Endodontics: A Cross-sectional Questionnaire-based Study - Marija Šimundić Munitić; Ivana Šutej; Nensi Ćaćić; Antonija Tadin; Merima Balić; Ivona Bago; Tina Poklepović Peričić (Acta Stomatologica Croatica, 2021)
Objectives: To assess dentists’ level of knowledge and practice concerning antibiotic usage in endodontics using the European Society of Endodontology position statement as a reference. Material and Methods: A cross-sectional study was conducted in the form of an electronic questionnaire consisting of 23 questions, including dentists’ demographic and professional characteristics, attitudes as well as experiences regarding antibiotics in endodontics. Data were evaluated by the Mann-Whit-ney test or the Kruskal Wallis 1-way ANOVA, α = 5%. Results: The overall mean self-reported knowl-edge of antibiotics usage in endodontics was 11.7±2.5 points, out of a maximum possible score of 23. The factors associated with a higher knowledge were: age (P≤0.001), clinical experience (P≤0.001), specialist training (P=0.008), and adherence to the guidance on the use of systemic antibiotics in endodontics (P=0.006). Dentists who specialized in endodontics (16.1±2.2) achieved higher levels of knowledge. Conclusion: Knowledge on antibiotic usage in endodontics among dentists in Croatia is insufficient. There is a need for continuing education on the use of antibiotics among general dentists.